Climate Change Projection and Its Impacts on Building Façades in Singapore - Chew, Lup Wai; Li, Xian-Xiang; Chew, Michael Y. L. (Sustainability, 2023)
Singapore is one of the most populous countries, and the majority of the population stays in high-rise public flats. In 2021, there were about 1.1 million public residential units, of which 79% were above 20 years old. The number of incidents of falling objects from a height has been increasing due to the aging and deterioration of buildings. The Periodic Façade Inspection (PFI) regime was enacted in 2020 to mandate façade inspections for all buildings above 13 m and exceeding 20 years old. However, the relatively new PFI regime has not considered the potential impacts of climate change on building façades. In this paper, the common root causes of façade defects that can be impacted by climate change are first identified. Based on the climate projection in Singapore to 2100, Singapore is expected to experience a higher mean temperature, a higher rainfall intensity, more extreme rainfall events, and a higher wind gust speed. Overall, these changes in the climate pattern will accelerate corrosion or degradation, material fatigue, adhesion failure, biological attack, and humidity or dampness. The impacts of climate change on vertical greeneries are also discussed. This paper provides a first insight into the key concerns to focus on for the future revision and improvement of the PFI regime to incorporate climate change impacts on façades.